Association of volatile anesthesia exposure and depth with emergence agitation and delirium in children: Prospective observational cohort study - Yinan Zhang; Yinan Zhang; Qiuying Zhang; Qiuying Zhang; Shan Xu; Shan Xu; Xiaoxi Zhang; Xiaoxi Zhang; Wenxu Gao; Yu Chen; Zhaoqiong Zhu; Zhaoqiong Zhu (Frontiers in Pediatrics, 2023)
BackgroundSevoflurane anesthesia is widely used in pediatric ambulatory surgery. However, emergency agitation (EA) and emergency delirium (ED), as major complications following sevoflurane anesthesia in children, pose risks to surgery and prognosis. Identifying the high risk of EA/ED, especially anesthesia exposure and the depth of anesthesia, may allow preemptive treatment.MethodsA total of 137 patients were prospectively enrolled in this single-center observational cohort study to assess the incidence of EA or ED. Multivariable logistic regression analyses were used to test the association between volatile anesthesia exposure and depth with EA or ED. The Richmond Agitation and Sedation Scale (RASS), Pediatric Anesthesia Emergence Delirium Scale (PAED) and Face, Legs, Activity, Cry, and Consolability (FLACC) behavioural pain scale was used to assess the severity of EA or ED severity and pain. Bispectral index (BIS) to monitor the depth of anesthesia, as well as TimeLOW−BIS/TimeANES %, EtSevo (%) and EtSevo-time AUC were included in the multivariate logistic regression model as independent variables to analyze their association with EA or ED.ResultsThe overall prevalence of EA and ED was 73/137 (53.3%) and 75/137 (54.7%) respectively, where 48/137 (35.0%), 19/137 (13.9%), and 6/137 (4.4%) had mild, moderate, and severe EA. When the recovery period was lengthened, the prevalence of ED and extent of FLACC decreased and finally normalized within 30 min in recovered period. Multivariable logistic regression demonstrated that intraoperative agitation [2.84 (1.08, 7.47) p = 0.034], peak FLACC [2.56 (1.70, 3.85) p < 0.001] and adverse event (respiratory complications) [0.03 (0.00, 0.29) p = 0.003] were independently associated with higher odds of EA. Taking EtSevo-time AUC ≤ 2,000 as a reference, the incidence of EA were [15.84 (2.15, 116.98) p = 0.002] times and 16.59 (2.42, 113.83) p = 0.009] times for EtSevo-time AUC 2,500–3,000 and EtSevo-time AUC > 3,000, respectively. Peak FLACC [3.46 (2.13, 5.62) p < 0.001] and intraoperative agitation [5.61 (1.99, 15.86) p = 0.001] were independently associated with higher odds of developing ED. EtSevo (%), intraoperative BIS value and the percentage of the duration of anesthesia at different depths of anesthesia (BIS ≤ 40, BIS ≤ 30, BIS ≤ 20) were not associated with EA and ED.ConclusionsFor pediatrics undergoing ambulatory surgery where sevoflurane anesthesia was administered, EA was associated with surgical time, peak FLACC, respiratory complications, and “EtSevo-time AUC” with a dose-response relationship; ED was associated with peak FLACC and intraoperative agitation.